Implementation of Sharia System in Sharia-Certified Hospitals - Warsidi, Warsidi; Haqqi, Abdurrahman Raden Aji; Swadjaja, Isma (Jurnal Ilmiah Ekonomi Islam, 2024)
DSN-MUI has granted Sharia certification to several entities that meet the criteria for being recognized as Sharia entities, including Muhammadiyah Hospital Lamongan. This hospital received the certificate from DSN-MUI with a score of 95% or an excellent rating, presented directly by KH. Ma’ruf Amin, the Chairman of MUI. This study aims to evaluate the implementation of Sharia principles at Muhammadiyah Hospital Lamongan, particularly inpatient services, based on maqasid shariah. The research employs a qualitative methodology, using data collection techniques such as observation, interviews, and documentation, which are then analyzed descriptively. The results indicate that the hospital has applied four mandatory provisions for Sharia hospital management according to the DSN-MUI Fatwa, including contracts, services, medications, food and beverages, cosmetics, other utility items, and fund management. Each provision is implemented by DSN-MUI standards and assessment criteria, demonstrating that Muhammadiyah Hospital Lamongan has successfully met the standards as a certified Sharia hospital and operates according to the established Sharia principles.